Assessment of prevalence and knowledge, attitude and practice regarding tobacco consumption among adolescents in rural field practice area of medical college in Telangana, India: a cross-sectional study - Tubachi, Aruna P.; Sotala, Madhusudhan; Reddy, S. C. K.; Paunikar, Swapnil (International Journal Of Community Medicine And Public Health, 2018)
Background: Tobacco is a major cause of premature death and disease worldwide. Over five million people die each year due to tobacco related illness- a figure expected increase by 8 million a year by 2030. Adolescence is transitional phase of growth and development between childhood and adulthood. WHO defines an adolescent as any person between ages 10 and 19. Adolescents consist of 16% of world population. Not only being productive age group they are also vulnerable to habit formation during this age group. The study was conducted to assess the prevalence and KAP regarding tobacco consumption among the adolescents. Methods: It is a cross sectional study where sampling was done by multistage random sampling conducted in 5 villages in the rural practice area of RVM medical college, Laxmakkapally, Telangana state. Results: Study population consists of 149 adolescents between the age of 10-19 years. Mean age of study participants was 16.6 years. 92.6% of participants were males. 66.4% were affiliated to school or college. 94% were aware that tobacco was hazardous. Knowledge regarding passive smoking as hazardous to health was present only in 75.8% of the population. Knowledge regarding anti-tobacco messages was low as 69.1%. 65.8% knew that it was illegal to smoke in public places. 18.8% of study population was engaged in tobacco consumption. Conclusions: Study concludes that tobacco consumption is high among the adolescents and its similar in rural Telangana as found in other states. Even though knowledge regarding hazards of tobacco consumption is high, knowledge regarding passive smoking is low. Attitude and practice regarding tobacco consumption is not satisfactory and awareness for the same is needed.